On Quiescent Reliable Communication - Chen, Wei (SIAM Journal on Computing, 29:6, April 2000, pp. 2040-2073., 2000)
We study the problem of achieving reliable communication with quiescent algorithms (i.e., algorithms that eventually stop sending messages) in asynchronous systems with process crashes and lossy links. We ﬁrst show that it is impossible to solve this problem in asynchronous systems (with no failure detectors). We then show that, among failure detectors that output lists of suspects, the weakest one that can be used to solve this problem is P, a failure detector that cannot be implemented. To overcome this diﬃculty, we introduce an implementable failure detector called Heartbeat and show that it can be used to achieve quiescent reliable communication. Heartbeat is novel: in contrast to typical failure detectors, it does not output lists of suspects and it is implementable without timeouts. With Heartbeat, many existing algorithms that tolerate only process crashes can be transformed into quiescent algorithms that tolerate both process crashes and message losses. This can be applied to consensus, atomic broadcast, k-set agreement, atomic commitment, etc.